153k views
5 votes
Show that (2, 1) is a solution of the system of equations.

x + 3y = 5,

y = –x + 3

Substitute (2, 1) into x + 3y = 5 to get
.
Simplify the equation to get
.
Substitute (2, 1) into y = –x + 3 to get
.
Simplify the equation to get
.

User Urbanhusky
by
4.7k points

2 Answers

5 votes

Answer:

The answer is

Step-by-step explanation:

D

A

A

A

User Jonprasetyo
by
4.6k points
3 votes

Answer:

1: D

2: A

3: A

4: A

Step-by-step explanation:

I got it as a question on an Edge Instruction (I'm in 8th grade)

User Thefreeman
by
4.7k points